Conserving the Kuttanad wetlands: stakeholder preferences of management alternatives - Sulakshana C Rao; R Balasubramanian (Agricultural Economics Research Review, 2023)
Multiple user groups benefit from wetland ecosystem services; therefore, conflicts of interest between stakeholders are common. Anthropogenic intervention has compromised wetlands and their conservation, and an institutional framework is urgently needed for using wetlands sustainably. This case study of the Kuttanad wetlands, framed to analyse stakeholders’ preferences of management alternatives for conservation, finds that all stakeholders prefer public management over the other institutional arrangements, and all prefer an improvement over the status quo. The stakeholders are willing to pay for conservation.